(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The protective role of Alpha Lipoicacide on cardio_renal function in rabbits subjected to Mesterolone was studied. A total of twenty adult female rabbits was divided into fourgroups:Control,Mesterolone(0.65mg/ kg B.w),Lipoic acid(10 mg/kg B.w) and Mesterolone +Lipoic acid.All animals received treatment every day for 60 days by oral administration during the period from 1stAugust 2018 to 1st June 2019. At the end of the experiment, animals were anesthetized by double dose anesthesia, heart and kidney tissues for RNA isolation were taken.This retrospective study was carried out in Department of physiology/College of Veterinary Medicine/University of Baghdad/Iraq. The heart and kidney tissue were isolated for the expression of atrial natriuretic peptide,nuclear factor erythroid 2 related factor 2 and Translocator protein genes.The results showed a significant increase in the expression of the genes in Mesterolonegroup.Whereas, Lipoic avid supplementation decreases them. These results indicate the important effect of Alpha lipoic acid on cardiorenal function. These anabolic androgenic steroids such as Mesterolone exert an up regulation of atrial natriuretic peptide,nuclear factor erythroid 2 related factor 2 and Translocator protein genes expression to overcome the damage of heart and kidney tissue induced by them.